On the Role of Mentalizing Processes in Aesthetic Appreciation: An ERP Study - Beudt, Susan; Jacobsen, Thomas (Frontiers in Human Neuroscience, 2015)
We used event-related brain potentials to explore the impact of mental perspective taking on processes of aesthetic appreciation of visual art. Participants (nonexperts) were first presented with information about the life and attitudes of a fictitious artist. Subsequently, they were cued trial-wise to make an aesthetic judgment regarding an image depicting a piece of abstract art either from their own perspective or from the imagined perspective of the fictitious artist (i.e., theory of mind condition). Positive self-referential judgments were made more quickly and negative self-referential judgments were made more slowly than the corresponding judgments from the imagined perspective. Event-related potential analyses revealed significant differences between the two tasks both within the preparation period (i.e., during the cue-stimulus interval) and within the stimulus presentation period. For the theory of mind condition we observed a relative centro-parietal negativity during the preparation period (700 – 330 ms preceding picture onset) and a relative centro-parietal positivity during the stimulus presentation period (700 – 1100 ms after stimulus onset). These findings suggest that different subprocesses are involved in aesthetic appreciation and judgment of visual abstract art from one’s own vs. from another person’s perspective.